"Pamięci, przemów" Vladimira Nabokova na tle pisarstwa autobiograficznego - Pogracka-Michalak, Izabela (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article treats of position of Vladimir Nabokov’s autobiography Pamięci, przemów against a background of autobiographical writing. The author recapitulates studies of autobiography researchers and analyses the chosen work from the point of view of classification to various type of autobiography.